1984
DOI: 10.1530/jrf.0.0700095
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of LH, prolactin, oestradiol-17  and progesterone in sows weaned after lactation for 10 or 35 days

Abstract: Piglets were weaned from multiparous sows at 10 days (Group E; N = 7) or 35 days (Group C; N = 8) of lactation. Blood samples were collected at 8 h intervals from the day before weaning (Day--1) until and including the day of first mating, then once daily until 10 days post coitum. Additionally, 5 sows in each group were sampled at 30 min intervals for 12 h on Days--1, 0 and 1, then at 30 min intervals for 6 h daily until mating, finally at 30 min intervals for 2 h daily until 5 days post coitum. Group E sows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
21
1

Year Published

1985
1985
1995
1995

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 23 publications
9
21
1
Order By: Relevance
“…The results of the present experiment confirm previous data from our laboratory showing that restricted feeding during lactation increases the duration of the rematins interval and reduces the rates of pregnaicy and embryo survival (Kirkwood et al 1981a(Kirkwood et al ,b, 1990 Edwards and Foxcroft (1983a,b) and Kirkwood et al (1984) (Smith 1986 For personal use only.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present experiment confirm previous data from our laboratory showing that restricted feeding during lactation increases the duration of the rematins interval and reduces the rates of pregnaicy and embryo survival (Kirkwood et al 1981a(Kirkwood et al ,b, 1990 Edwards and Foxcroft (1983a,b) and Kirkwood et al (1984) (Smith 1986 For personal use only.…”
Section: Discussionsupporting
confidence: 91%
“…Key words: Sows, feed intake, estrus, GnRH Notably, both short lactation lengths (Kirkwood et al 1984a) and low feed intakes during lactation (Kirkwood et al 1987 (Reese et al 1982) and in a reduction in pregnancy rates (Kirkwood et al 1987). …”
mentioning
confidence: 99%
“…Studies with sows having short lactation lengths have also demonstrated a decrease in embryo numbers (Cole et al 1975). This may be a result of an attenuated luteinizing hormone (LH) surge at estrus, adversely affecting subsequent follicular luteinization (Kirkwood et al 1984a). Kirkwood et al (1984a) suggested that adverse effects on luteinization could influence gestation steroid profiles which, via an influence on the uterine environment, may influence embryo viability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have indicated that, after weaning, increases in gonadotropins cause follicular growth which results in elevated concentrations of circulating estrogens (6,7,8,9). Increasing concentrations of estrogen in peripheral cir culation appear to be the major trigger for the preovulatory surge of gonad otropins and subsequent ovulation (5,10,11).…”
Section: Introductionmentioning
confidence: 99%